Thieves in court the making of the German legal system in the nineteenth century - Habermas, Rebekka 1959-2023 (Publications of the German Historical Institute, 2016)
From the seemingly insignificant theft of some bread and a dozen apples in nineteenth century rural Germany, to the high courts and modern-day property laws, this English-language translation of Habermas' Diebe vor Gericht explores how everyday incidents of petty stealing and the ordinary people involved in these cases came to shape the current legal system. Habermas draws from an unusual cache of archival documents of theft cases, tracing the evolution and practice of the legal system of Germany through the nineteenth century. This close reading, relying on approaches of legal anthropology, challenges long-standing narratives of legal development, state building, and modern notions of the rule of law. Ideal for legal historians and scholars of modern German and nineteenth-century European history, this innovative volume steps outside the classic narratives of legal history and gives an insight into the interconnectedness of social, legal and criminal history